The Bahamas : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Bahamas. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that economic growth in The Bahamas is estimated to have stalled in 2015, as a modest increase in air tourism arrivals was not sufficient to offset a contraction in domestic demand and weak exports of goods. Private consumption and investment were weighed down by headwinds from fiscal consolidation, as well as an end to construction. Inflation was moderate at 1.9 percent on average in 2015. Growth is expected to strengthen to about 0.5 percent in 2016, supported by continued growth in air tourist arrivals and moderating headwinds to private consumption and investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet